Motor neuron disease and polio in Scotland. - Swingler, R J (1992)
An analysis of mortality and morbidity rates for motor neuron disease (MND) in Scotland has confirmed earlier observations that the disease is more common in men and older age groups. The geographical distribution is non-uniform and related to discharge rates for all neurological diseases. Discharge and mortality rates are increasing but there has been no decline in populations who would have been vaccinated against polio.